Fermentation and Spoilage Yeasts and their Relevance for the Beverage Industry – A Review - Hutzler, Mathias; Riedl, Robert; Koob, Jennifer; Jacob, Fritz (BrewingScience, 2012)
During the production of beverages or in terms of quality control, the question often arises as to which yeast species occur in which beverage as starter cultures or as spoilers? The species name should direct beverage microbiologists and technologists to information that is available about species? specific spoilage and fermentation characteristics. This review provides an overview regarding the yeast flora present in beverage processes in general and provides guidance on how this yeast flora can be identified at the level of genus, species or strain. Additionally, beverage-specific technological and microbiological information about specific yeast species is included. This review also provides an overview of the literature and information on the methods currently available for species identification from the point of view of beverage production, designed to aid microbiologists or technologists in coping with the challenges they face. Descriptions of the yeast flora found in beer, wine, sparkling wine and the mash used for the production of distilled beverages, as well as indigenous fermented beverages are provided below. Yeasts are grouped as either inoculated or spontaneous starter cultures and as direct or indirect spoilage organisms. Spoilage yeasts present in carbonated soft drinks are classified according to their spoilage and fermentative potential in a specific matrix. Detailed information about beverage-relevant characteristics is summarized in alphabetical order according to yeast genus and species name. Fermentation characteristics, fermentation by-products, sources of spoilage, resistance to preservatives and ethanol, osmotolerance, growth conditions and temperatures, characteristics in culture media and other beverage-specific background information are described.